Le choro, musique métisse et originelle : transferts culturels, hybridations et identité culturelle nationale au Brésil (1870-1930) - Alice Boccara (Les Cahiers ALHIM)
Born in Rio de Janeiro in the 1970s, the musical genre of choro is one of the three genres at the roots of all Brazilian music. It transcends the limits between popular music and art music while having a special place among Brazilian musics, being considered as an original genre, at the roots of the Brazilian musical identity and that condenses its mixed descents – Amerindian, African, European. From the premises of the apparition of the genre (at the end of the 19th century) to the 1930s when the choro had already become a musical genre on its own with its fixed canon and repertoire: within this historical frame, the purpose of this article is to articulate a musicological view (about the questions concerning the dialectical relationship between the fixation of the generic boarders of the genre and its capacity to integrate and to influence new genres and musical languages), along with a historical view about the question of miscegenation and the social valorization of this notion in Brazil. Hence, this article focuses on the choro by proposing an attempt to contemplate a music that is both from a mixed descent and at the foundations of a national cultural identity.